Homopropargyl as a new recognition moiety of a fluorescent probe for detection of palladium in living cells. Issue 32 (22nd July 2019) - Chen, Miao; Wang, Xianhui; Wang, Nannan; Ji, Xin; He, Jinling; Zhang, Jian; Zhao, Weili
Abstract : Palladium contamination has attracted widespread attention due to the toxicity and the wide use of palladium species. Abstract : Palladium contamination has attracted widespread attention due to the toxicity and the wide use of palladium species. Consequently, development of convenient and effective methods for palladium detection is of great importance. Herein, a BODIPY-based fluorescent probe containing a meso homopropargyl ester substituent as a new recognition moiety for detection of Pd 2+ was developed. The probe could be used to detect Pd 2+ in acetonitrile/PBS buffer (1 : 99 v/v, 10 mM, pH 7.4) at 37 °C with high selectivity and sensitivity. The detection limit of probe1 toward Pd 2+ was estimated to be 50.8 nM. Furthermore, probe1 was successfully applied for detection of Pd 2+ in living cells, indicating good potential application prospects.